Undoing Equivalence: Rethinking Carbon Accounting for Just Carbon Removal - Carton, Wim; Lund, Jens Friis; Dooley, Kate (Frontiers in Climate, 2021)
Concerns are increasingly raised over the centrality of carbon removal in climate policy, particularly in the guise of ‘net-zero’ targets. Most significantly perhaps, treating emissions and removals as equivalent obscures emission reductions, resulting in ‘mitigation deterrence’. Yet the conflation of emission reductions and removals is only one among several implicit equivalences in carbon removal accounting. Here we examine three other forms – carbon, geographical and temporal equivalence - and discuss their implications for climate justice and the environmental risks with carbon removal. We conclude that ‘undoing’ these equivalences would further a just response to the climate crisis and tentatively explore what such undoing might look like in practice.